PENINGKATAN KEMAMPUAN BERNYANYI DENGAN MEDIA AUDIO VISUAL DI SMP 18 PADANG - Fadhilla Tirrahmah; Ardipal Ardipal; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2013)
Abstract This research aimed at determining the effect of audio visual media on students’ ability in singing national anthems. The subject of the research were students of VIII2 at SMP Negeri 18 Padang in the year of 2012-2013. The design of the research was class action research in which students’ musical notations learning by using the audio visual determined. The research findings showed that there was an improvement on students’ singing. The improvement was seen from the average score of the class in each cycle. In the pre-cycle, the average score of the students was 68.375. In the first cycle, the average score was improved to 75.375 and in the second cycle, it was improved to 82.25. It was concluded that audio visual media were appropriate for students’ singing improvement. Kata kunci: bernyanyi, notasi, media, audio, visual.